EARNINGS VOLATILITY AND CAPITAL STRUCTURE: EMPIRICAL EVIDENCE OF NON-FINANCIAL FIRMS OF PAKISTAN - MUHAMMAD ILYAS; DR. MUHAMMAD JEHANGIR; DR. ADNAN AHMAD (Journal of Business & Tourism, 2021)
In this research investigated capital structure and earning volatility. For this purpose, selected a sample of 267 firms listed on Karachi Stock exchange1 during 2006-2014.Data are panel in nature, therefore used panel data techniques for analysis. Moreover, selected the fixed effect model on the basis of diagnostic tests result. Finally, the results demonstrate that earnings volatility negatively and significantly affect the capital structure of sample firms. Thus, concluded that high volatility reduces the confidence level of creditors.